Wavelength-dependent nonlinear optical loop mirror for simultaneous amplitude noise reduction at two wavelengths - Pottiez O.; Ibarra-Escamilla B.; Kuzin E. A. (Journal of the European Optical Society-Rapid Publications, 2013)
We propose and study analytically and numerically a polarisation-imbalanced Nonlinear Optical Loop Mirror (NOLM) scheme exhibiting a wavelength-dependent nonlinear characteristic. The device includes a symmetric coupler, an isotropic (or, in practice, twisted non-polarisation-maintaining) fibre loop and a section of high birefringence (HiBi) fibre to break the polarisation symmetry. Thanks to the wavelength-dependent phase shift of the HiBi fibre, wavelength-dependent switching is obtained. For proper orientation of the HiBi fibre in the loop plane and using linear input polarisation at 45° with respect to its birefringence axes, the NOLM switching power varies with wavelength, whereas its zero low-power transmission and 100% maximal transmission are constant. Through slight adjustments of the HiBi fibre birefringence, which can be realised mechanically or thermally, the ratio between switching powers at two particular wavelengths can be readily adjusted. We show numerically that this scheme can be applied to simultaneous amplitude regeneration of two wavelength channels exhibiting uneven power levels.